Increasing Revenue through Instagram, Shopee, TikTok, and WhatsApp Applications from a Sharia Economic Perspective: (Case Study of Rabbani Wonosobo Store) - Nurmadinda, Adinda Rania; Zakiyah, Septiyani; Indriati, Husnia; Hinawati, Titik (UM Purwokerto Press, 2025)
In today’s digital era, social media and e-commerce platforms such as Instagram, Shopee, TikTok, WhatsApp have become important tools for small and medium enterprises to expand their market reach and increase revenue. Instagram as the main information medium, which becomes the access to review other platforms used. Shopee is used as the main e-commerce platform, where customers can choose the products they want. The TikTok application is used as a medium for marketing creative content, while WhatsApp is used as a communication tool between sellers and buyers. This study aims to analyze the effectiveness of using the Instagram, Shopee, TikTok, and WhatsApp applications in increasing the revenue of Rabbani Wonosobo stores and evaluating their compliance with the principles of Islamic economics in running their business. The method used is a qualitative approach with a case study method at Rabbani Wonosobo shop. Data obtained through interviews with leaders, direct observation, and analysis of income levels before and after application use. In addition, researchers also used a literature review to find out the economic aspects of sharia. The results of the study show that digitalization helps marketing so that it can increase revenue at the Rabbani Wonosobo store, besides that in running its business, the Rabbani Wonosobo store always prioritizes sharia economic values.